Peran Istri Generasi Milenial Perspektif Gender dan Hukum Keluarga Islam: Studi Kasus di Kelurahan Mawang Kecamatan Somba Opu Kab Gowa - Andi Marwah; Andi Muhammad Akmal; Alimuddin Alimuddin (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the role of millennial wives in the perspective of gender and Islamic family law in Mawang Village, Somba Opu District, Gowa Regency. The focus of the research includes the role of millennial wives, the perception of community leaders on gender equality in social reality, and the view of Islamic family law on this role. This type of research is qualitative with an empirical juridical approach. The data sources came from 10 main informants of millennial wives and 5 supporting informants consisting of the Village Head and the Head of RT. Data collection techniques are carried out through observation, interviews, documentation, and reference tracing, while data analysis uses the stages of data reduction, data presentation, and conclusion drawn. The results of the study show a significant shift in the role of millennial wives compared to previous generations, where wives not only play a role in the domestic sphere, but are also active in the public sector as workers and contributors to the family economy. The perception of community leaders shows a progressive attitude towards gender equality while still emphasizing Islamic values. The perspective of Islamic family law also views that millennial wives are allowed and even encouraged to carry out their domestic and public roles in a balanced manner as long as they do not neglect their obligations as wives. In conclusion, the dual role of millennial wives is an acceptable social reality within the framework of gender and Islamic family law as long as it is carried out in a proportionate and harmonious manner.